Amyloid Transition of Ubiquitin on Silver Nanoparticles Produced by Pulsed Laser Ablation in Liquid as a Function of Stabilizer and Single‐Point Mutations. Issue 34 (24th July 2014) - Mangini, Vincenzo; Dell'Aglio, Marcella; Stradis, Angelo De; Giacomo, Alessandro De; Pascale, Olga De; Natile, Giovanni; Arnesano, Fabio
Abstract The interaction of nanoparticles with proteins has emerged as a key issue in addressing the problem of nanotoxicity. We investigated the interaction of silver nanoparticles (AgNPs), produced by laser ablation with human ubiquitin (Ub), a protein essential for degradative processes in cells. The surface plasmon resonance peak of AgNPs indicates that Ub is rapidly adsorbed on the AgNP surface yielding a protein corona; the Ub‐coated AgNPs then evolve into clusters held together by an amyloid form of the protein, as revealed by binding of thioflavin T fluorescent dye. Transthyretin, an inhibitor of amyloid‐type aggregation, impedes aggregate formation and disrupts preformed AgNP clusters. In the presence of sodium citrate, a common stabilizer that confers an overall negative charge to the NPs, Ub is still adsorbed on the AgNP surface, but no clustering is observed. Ub mutants bearing a single mutation at one edge β strand (i.e. Glu16Val) or in loop (Glu18Val) behave in a radically different manner.